4ln(3x-5)3=18

Simple and best practice solution for 4ln(3x-5)3=18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4ln(3x-5)3=18 equation:


Simplifying
4ln(3x + -5) * 3 = 18

Reorder the terms:
4ln(-5 + 3x) * 3 = 18

Reorder the terms for easier multiplication:
4 * 3ln(-5 + 3x) = 18

Multiply 4 * 3
12ln(-5 + 3x) = 18
(-5 * 12ln + 3x * 12ln) = 18
(-60ln + 36lnx) = 18

Solving
-60ln + 36lnx = 18

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Reorder the terms:
-18 + -60ln + 36lnx = 18 + -18

Combine like terms: 18 + -18 = 0
-18 + -60ln + 36lnx = 0

Factor out the Greatest Common Factor (GCF), '6'.
6(-3 + -10ln + 6lnx) = 0

Ignore the factor 6.

Subproblem 1

Set the factor '(-3 + -10ln + 6lnx)' equal to zero and attempt to solve: Simplifying -3 + -10ln + 6lnx = 0 Solving -3 + -10ln + 6lnx = 0 Move all terms containing l to the left, all other terms to the right. Add '3' to each side of the equation. -3 + -10ln + 3 + 6lnx = 0 + 3 Reorder the terms: -3 + 3 + -10ln + 6lnx = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -10ln + 6lnx = 0 + 3 -10ln + 6lnx = 0 + 3 Combine like terms: 0 + 3 = 3 -10ln + 6lnx = 3 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| -20x+29=20x+29 | | (x-7)(x+2)=17 | | 19x+16=86 | | p-13=31 | | a(x)+b=c | | 7e-4(6+2w)=3(w-8) | | -4(5x-7)+1=20x+29 | | 25x+20=78 | | 47x=46x+1 | | 60+4n=76 | | 40x+18=86 | | 3(x+2)-8x=4x+1 | | 20x-10=110 | | 30x-18=150 | | 12=v+2 | | (4+4i)+(-5+7i)-8i= | | 8(-3b+6)=96 | | 1.3n-.03=9 | | 4xy^2/y | | 20×1/4 | | x^2-40=41 | | 3(2l+10)=48 | | y+x=10-4 | | 3x+22=x+4 | | 0.6(x-1)+0.2x=6.6 | | y=-2.1x+3.4 | | -x-19=2x+8 | | 49=-7z | | y=2x^2-36x+c | | -2(x+2)+3=3(x+3)+4 | | (x-2)(x-2)+(y-6)(y-6)=25 | | 2+f=-3 |

Equations solver categories